Multifunctional body position pillow - HE MANMAN; WANG JIE; SHI ZHIJING; YAO QIUPING (2024)
The invention discloses a multifunctional body position pillow, and particularly relates to the field of bedding articles, the multifunctional body position pillow comprises a pillow body, the top of the pillow body is provided with a protruding part used for supporting the neck, a plurality of first air holes are uniformly formed in the protruding part, a supporting insertion block is inserted in the pillow body and located below the protruding part, and an insertion plate is inserted in the supporting insertion block; a plurality of placing grooves are formed in the top of the inserting plate in the horizontal direction at equal intervals, an effect bag is placed in each placing groove, a plurality of second air holes are formed in the top of the supporting inserting block, and pillow surface cloth is connected to the upper portion of the pillow body. According to the pillow, the pillow surface cloth with the dirty surface after being used for a period of time can be conveniently detached and taken down to